Comparative therapeutic efficacy of remdesivir and combination lopinavir, ritonavir, and interferon beta against MERS-CoV - Timothy P. Sheahan (Nature Portfolio, 2020)
Remdesivir (RDV) is a broad-spectrum antiviral drug with activity against MERS coronavirus, but in vivo efficacy has not been evaluated. Here, the authors show that RDV has superior anti-MERS activity in vitro and in vivo compared to combination therapy with lopinavir, ritonavir and interferon beta and reduces severe lung pathology.